Proceedings of the 2018 Conference of the North American Chapter Of the Association for Computational Linguistics: Hu 2018
DOI: 10.18653/v1/n18-1024
|View full text |Cite
|
Sign up to set email alerts
|

Neural Automated Essay Scoring and Coherence Modeling for Adversarially Crafted Input

Abstract: We demonstrate that current state-of-theart approaches to Automated Essay Scoring (AES) are not well-suited to capturing adversarially crafted input of grammatical but incoherent sequences of sentences. We develop a neural model of local coherence that can effectively learn connectedness features between sentences, and propose a framework for integrating and jointly training the local coherence model with a state-of-the-art AES model. We evaluate our approach against a number of baselines and experimentally de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
43
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 64 publications
(52 citation statements)
references
References 15 publications
0
43
0
1
Order By: Relevance
“…Extensive research has been done on text coherence, motivated by downstream utility of coherence models. In addition to the applications we demonstrate in Section 4, established applications include determining the readability of a text (coherent texts are easier to read) (Barzilay and Lapata, 2008), refinement of multi-document summaries (Barzilay and Elhadad, 2002), and essay scoring (Farag et al, 2018).…”
Section: Related Workmentioning
confidence: 99%
“…Extensive research has been done on text coherence, motivated by downstream utility of coherence models. In addition to the applications we demonstrate in Section 4, established applications include determining the readability of a text (coherent texts are easier to read) (Barzilay and Lapata, 2008), refinement of multi-document summaries (Barzilay and Elhadad, 2002), and essay scoring (Farag et al, 2018).…”
Section: Related Workmentioning
confidence: 99%
“…Taghipour (2017) suggests using contextfree grammars, and language modeling to create spurious essays, before trying to detect whether an input essay is spurious or not. Farag et al (2018) construct adversarial essays by permuting the sentences of good scoring essays.…”
Section: Adversarial Essaysmentioning
confidence: 99%
“…These problems (and the success of deep learning in other areas of language processing) have led to the development of neural methods for automatic essay scoring, moving away from feature engineering. A variety of studies (mostly LSTM-based) have reported AES performance comparable to or better than feature-based models (Taghipour and Ng, 2016;Cummins and Rei, 2018;Wang et al, 2018;Jin et al, 2018;Farag et al, 2018;Zhang and Litman, 2018). However, the current state-of-the-art models still use a combination of neural models and hand-crafted features (Liu et al, 2019).…”
Section: Introductionmentioning
confidence: 99%